Glances in Immunology of HIV and HCV Infection - Quaranta, Maria Giovanna (Hindawi Publishing Corporation, 2012)
Since the identification of HIV and HCV much progress has been made in the understanding of their life cycle and interaction with the host immune system. Despite these viruses markedly differ in their virological properties and in their pathogenesis, they share many common features in their immune escape and survival strategy. Both viruses have developed sophisticated ways to subvert and antagonize host innate and adaptive immune responses. In the last years, much effort has been done in the study of the AIDS pathogenesis and in the development of efficient treatment strategies, and a fatal infection has been transformed in a potentially chronic pathology. Much of this knowledge is now being transferred in the HCV research field, especially in the development of new drugs, although a big difference still remains between the outcome of the two infections, being HCV eradicable after treatment, whereas HIV eradication remains at present unachievable due to the establishment of reservoirs. In this review, we present current knowledge on innate and adaptive immune recognition and activation during HIV and HCV mono-infections and evasion strategies. We also discuss the genetic associations between components of the immune system, the course of infection, and the outcome of the therapies.